Rock-Breaking Laws of Disc Cutters with Different Height Differences in Hard Rock Strata - Zelin Lu; Xuchun Wang; Hongwei Teng; Xiaoming Guan; Chen Song; Gang Fan (Advances in Civil Engineering)
When shield machine traverses through hard rock mass, disc cutters will be abraded to different degrees. Excessive height difference exists between adjacent disc cutters, which critically affects the rock-breaking efficiency. Relying on a shield section of hard rock mass in Qingdao, the disc cutter abrasions are measured on site, and the reason for low construction efficiency is analysed. Subsequently, the discrete element method is used to study the rock-breaking law under different height differences of disc cutters. The ultimate cutter height difference for rock breaking is obtained. According to this, the cutter adjustment scheme is proposed to reduce the cutter height differences on site. Comparing shield tunnelling parameters before and after the cutter adjustment, it is found that the construction efficiency is significantly improved. The results are of great significance for improving the rock-breaking efficiency and increasing advancing speed of shield in hard rock mass.